Difference in Housing Temperature‐Induced Energy Expenditure Elicits Sex‐Specific Diet‐Induced Metabolic Adaptations in Mice. Issue 10 (28th August 2020) - Morris, E. Matthew; Noland, Roberto D.; Allen, Julie A.; McCoin, Colin S.; Xia, Qing; Koestler, Devin C.; Shook, Robin P.; Lighton, John R. B.; Christianson, Julie A.; Thyfault, John P.
Abstract : Objective: The aim of this study was to test whether increased energy expenditure (EE), independent of physical activity, reduces acute diet‐induced weight gain through tighter coupling of energy intake to energy demand and enhanced metabolic adaptations. Methods: Indirect calorimetry and quantitative magnetic resonance imaging were used to assess energy metabolism and body composition during 7‐day high‐fat/high‐sucrose (HFHS) feeding in male and female mice housed at divergent temperatures (20°C vs. 30°C). Results: As previously observed, 30°C housing resulted in lower total EE and energy intake compared with 20°C mice regardless of sex. Interestingly, housing temperature did not impact HFHS‐induced weight gain in females, whereas 30°C male mice gained more weight than 20°C males. Energy intake coupling to EE during HFHS feeding was greater in 20°C versus 30°C housing, with females greater at both temperatures. Fat mass gain was greater in 30°C mice compared with 20°C mice, whereas females gained less fat mass than males. Strikingly, female 20°C mice gained considerably more fat‐free mass than 30°C mice. Reduced fat mass gain was associated with greater metabolic flexibility to HFHS, whereas fat‐free mass gain was associated with diet‐induced adaptive thermogenesis. Conclusions: These data reveal that EE and sex interact to impact energy homeostasis and metabolic adaptation to acute HFHS feeding, altering weight gain and body composition change. Abstract : Male and female mice housed at 30°C had lower energy expenditure (EE) and energy intake (EI) while having greater energy balance (EB) during 7‐day high‐fat/high‐sucrose (HFHS) feeding compared with male and female mice, respectively, housed at 20°C. However, female mice had lower energy balance compared with males at both housing temperatures. Female mice housed at 30°C gained less weight than 30°C males but gained the same relative amount of fat mass during acute HFHS feeding. Interestingly, 20°C females gained the same amount of weight as 20°C males but gained primarily fat‐free mass, whereas the males gained the same proportion of fat as 30°C males and females.